Neurobehavioral Effects of Levetiracetam in Patients with Traumatic Brain Injury - Benge, Jared F.; Phenis, Richard; Bernett, Abigail; Cruz, Daniel; KIRMANI, BATOOL F. (Frontiers in Neurology, 2013)
Moderate to severe traumatic brain injury (TBI) is one of the leading causes of acquired epilepsy. Prophylaxis for seizures is the standard of care for individuals with moderate to severe injuries at risk for developing seizures, though relatively limited comparative data is available to guide clinicians in their choice of agents. There have however been experimental studies which demonstrate potential neuroprotective qualities of levetiracetam after TBI, and in turn there is hope that eventually such agents may improve neurobehavioral outcomes post-TBI. This mini-review summarizes the available studies and suggests areas for future studies.